The Autecology of Genus Dischidia (Asclepiadaceae) in Bangka Island: Characteristics of Vegetation and Abiotic Environmental Factors Affecting Abundance - Yuliani Hajari; Sulistijorini Sulistijorini; Nunik Sri Ariyanti (Journal of Tropical Life Science, 2018)
Dischidia is an epiphytic plant, it is used as herbal medicine and has economic value. In addition, Dischidia also has an ecological function. Moreover, some species of Dischidia are endemic in a particular region. Various forest types occur in Bangka Island serves as natural habitat for this epiphytic plant. This research aimed to record the diversity and abundance of Dischidia and analyze those environmental factors which affect its abundance. The research was conducted in August – September 2016 at Bangka Island. Three plots of 20 × 20 m² were placed with a minimum interval of 50 m in the habitat where Dischidia are found. The species diversity and abundance of Dischidia as well as abiotic factors such as temperature, humidity, light intensity, wind speed, and altitude were recorded in these plots. The vegetation structure was analyzed based on index of diversity, index of dominancy and index of evenness. Data on the environmental condition and abundance of Dischidia were then analyzed using Canonical Correspondence Analysis (CCA) method with Canoco 4.5 software. Five species of Dischidia were found in Bangka Island that are Dischidia bengalensis, Dischidia imbricate, Dischidia nummularia, Dischidia rafflesiana, and Dischidia hirsute. Dischidia is found in 14 species of host plants. D. imbricate (23 individual plants) occurred in the heath forest at Pejem showed the highest abundance. Epiphytic fern plants, the Asplenium nidus (27 individual plants), was the dominant epiphytes found in the host tree of Dischidia The CCA showed that light intensity, temperature and humidity influenced the abundance of Dischidia.